Investigation of Native Speaker and Second Language Learner Intuition of Collocation Frequency. Issue 3 (3rd July 2015) - Siyanova‐Chanturia, Anna; Spina, Stefania
<x xml:space="preserve">Abstract</x> Research into frequency intuition has focused primarily on native (L1) and, to a lesser degree, nonnative (L2) speaker intuitions about single word frequency. What remains a largely unexplored area is L1 and L2 intuitions about collocation (i.e., phrasal) frequency. To bridge this gap, the present study aimed to answer the following question: How do L2 learners and native speakers compare against each other and corpora in their subjective judgments of collocation frequency? Native speakers and learners of Italian were asked to judge 80 noun‐adjective pairings as one of the following: high frequency, medium frequency, low frequency, very low frequency. Both L1 and L2 intuitions of high frequency collocations correlated strongly with corpus frequency. Neither of the two groups of participants exhibited accurate intuitions of medium and low frequency collocations. With regard to very low frequency pairings, L1 but not L2 intuitions were found to correlate with corpora for the majority of the items. Further, mixed‐effects modeling revealed that L2 learners were comparable to native speakers in their judgments of the four frequency bands, although some differences did emerge. Taken together, the study provides new insights into the nature of L1 and L2 intuitions about phrasal frequency.